Hubungan Tingkat Pengetahuan Ibu Hamil dan Kunjungan K4 Ibu Hamil Trimester 3 dengan Pemberian ASI Eksklusif Usia 0 - 6 Bulan di Puskesmas Tanah Merah Kabupaten Boven Digoel Papua Selatan - Adriana Herlina; Nanik Yuliwati (Universitas Malahayati Lampung, 2024)
ABSTRACT Providing knowledge of third trimester pregnant women during K4 about the importance of exclusive breastfeeding for the growth and development of children, especially children aged 0-6 months. Exclusive breastfeeding contains LPUFAs, FE, Minerals, Sodium, Calcium, Phosphorus, Magnesium, Lactobacillus Taurine, Water, Antibodies, Colostrum, Macrophage Cells, Neutrophil Cells, Lysozyme, Lactiferin, and Protein. Based on the above, the researcher is interested in conducting research entitled